2017
DOI: 10.1088/2058-8585/aa5c6d
|View full text |Cite
|
Sign up to set email alerts
|

A review of thin-film transistors/circuits fabrication with 3D self-aligned imprint lithography

Abstract: Nanoimprint lithography (NIL) is a promising method for the fabrication of micro/nanostructures through a simple, low-cost, and high throughput process. Imprinted 2D structure with high resolution has been demonstrated successfully for certain applications including magnetic hard disks and optical gratings. Manufacturing low-cost electronic devices that require patterned multi-layers with NIL is very challenging, particularly for those requiring different patterns. In recent years, considerable effort has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…FTM demonstrates many practical benefits; it requires the use of cost-effectively and widely available materials (Eg, Gl and water); it has already been reported to show compatibility with a wide range of thiophene-based polymers and solvents (toluene, chloroform, tetrahydrofuran, dichloromethane, etc) [9][10][11][12][13]; only a small amount of polymer solution (∼20 μl) is required to obtain well-aligned floatingfilms [8,9]; multilayer thin films can be formed using a single floating-film [8,11,21], etc. Despite all these advantages, some areas of the present platform of FTM require improvement compared to other developed methods, such as Langmuir Blodgett [33], ink-jet printing [34] and lithography [35]. For instance, the present platform only allows formation of ~three thin films using one floating-film, and the circular orientation of the floating-film also poses difficulty for practical applications.…”
Section: Organic Field-effect Transistors (Ofets)mentioning
confidence: 99%
“…FTM demonstrates many practical benefits; it requires the use of cost-effectively and widely available materials (Eg, Gl and water); it has already been reported to show compatibility with a wide range of thiophene-based polymers and solvents (toluene, chloroform, tetrahydrofuran, dichloromethane, etc) [9][10][11][12][13]; only a small amount of polymer solution (∼20 μl) is required to obtain well-aligned floatingfilms [8,9]; multilayer thin films can be formed using a single floating-film [8,11,21], etc. Despite all these advantages, some areas of the present platform of FTM require improvement compared to other developed methods, such as Langmuir Blodgett [33], ink-jet printing [34] and lithography [35]. For instance, the present platform only allows formation of ~three thin films using one floating-film, and the circular orientation of the floating-film also poses difficulty for practical applications.…”
Section: Organic Field-effect Transistors (Ofets)mentioning
confidence: 99%
“…Therefore, the hierarchical design was simplified into 2-D (in-plane) structures to enable practical fabrication by nanoimprint lithography. [50,51] Although the vertical randomness in height is preferable for anti-grating, [46] we previously demonstrated that 2-D randomness combined with binary height also provides sufficient phase variations for anti-grating, allowing for this simplification. [52] Figure 1d illustrates the cross section of the simplified design, wherein 2-D nanopatterns composed of random widths and binary height were created on either surface.…”
Section: Morpho-type Diffusersmentioning
confidence: 99%
“…To fabricate the designed diffusers, we employed nanoimprint lithography as it can create well-defined nanostructures at high throughput. [50,51] The fabrication process is depicted in Figure 4. First, silicon molds containing the negative-type nanopatterns were prepared by lithography and dry etching; we performed ebeam lithography for prototyping in this study.…”
Section: Fabricationmentioning
confidence: 99%
“…Hitherto, a variety of micro/nanoscale manufacturing technologies have been developed. For example, lithography is a typical method whose resolution can reach tens of nanometers and is widely used to manufacture high resolution functional structures [9,10]. However, the cost of mask, complex processing steps, expensive equipment and ultra-clean environment limit its extensive application [11].…”
Section: Introductionmentioning
confidence: 99%